(untitled) (American International Journal of Humanities, Arts and Social Sciences, 2023)
This study explores the imperative of fostering Trust to enhance the organizational performance of local authorities in Malaysia. Recognizing Trust as a pivotal factor, the research delves into strategies for strengthening interpersonal relationships and institutional credibility. By addressing trust deficits, the study aims to provide actionable insights that can contribute to the overall effectiveness and efficiency of local governance in Malaysia. The primary focus of this research is to put into practice the idea of Trust, precisely honing in on the effectiveness of local authorities (LAs) in Malaysia. In this instance, the study employs the Community Integrity Building (CIB) concept, emphasizing the pivotal roles played by community monitors, contractors, and LAs in collectively navigating toward improved performance. It offers a continuous feedback mechanism that enhances understanding and improves Trust in services provided by the LAs. The paper objectively explores the measuring of Trust, therefore linking the vacuum between conceptualization and realization, which is hardly seen in LAs. Finally, it concludes by reflecting some insights on the potential of the CIB approach regarding the trust agenda towards building a more progressive and dynamic new public management ecosystem in a Malaysian organization setting. JEL Classification Codes: D73.